2021
DOI: 10.1002/ijgo.13713
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine acceptance in pregnant women

Abstract: Objective To determine vaccine acceptance and hesitancy attitudes toward coronavirus disease 2019 (COVID‐19) vaccines in pregnant women. Methods Three hundred pregnant women were surveyed face to face with 40 questions. Sociodemographic characteristics, vaccination history, perception of risk for the COVID‐19 pandemic, the impact of the COVID‐19 pandemic, and acceptance of and attitude toward future COVID‐19 vaccination were prospectively evaluated. Results Among all participants, 111 (37%) stated their intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
193
7
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(275 citation statements)
references
References 20 publications
(43 reference statements)
16
193
7
7
Order By: Relevance
“…Pregnant women were excluded from preauthorization clinical trials, and only very limited human data on safety and efficacy during pregnancy were available at the time that the vaccines were authorized for use. Survey data before COVID-19 vaccine authorization showed low acceptance of COVID-19 vaccination among pregnant women, and the most frequently reported reasons for lack of intent to get vaccinated during pregnancy were limited safety data in pregnancy and concerns about possibility of harm to the fetus †† ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women were excluded from preauthorization clinical trials, and only very limited human data on safety and efficacy during pregnancy were available at the time that the vaccines were authorized for use. Survey data before COVID-19 vaccine authorization showed low acceptance of COVID-19 vaccination among pregnant women, and the most frequently reported reasons for lack of intent to get vaccinated during pregnancy were limited safety data in pregnancy and concerns about possibility of harm to the fetus †† ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…42 Previous studies investigating the acceptance of taking the COVID-19 vaccine have shown similar results. 30,40,[43][44][45] One study conducted in Turkey in 2021 reported a lower rate of COVID-19 vaccine acceptability, with only 37% stating that they intend to receive the vaccine if it were recommended for pregnant women. 45 Similar results were reported in a large study that included 16 countries across the world, with only 52.0% of pregnant women reporting that they will take the vaccine compared to 73.4% of nonpregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…30,40,[43][44][45] One study conducted in Turkey in 2021 reported a lower rate of COVID-19 vaccine acceptability, with only 37% stating that they intend to receive the vaccine if it were recommended for pregnant women. 45 Similar results were reported in a large study that included 16 countries across the world, with only 52.0% of pregnant women reporting that they will take the vaccine compared to 73.4% of nonpregnant women. 30 These results can be explained by the fact that people have concerns regarding the effectiveness and the safety of the vaccine, especially that the vaccine was developed rapidly and received accelerated approval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations